Surface intercalated spherical MoS2xSe2(1−x) nanocatalysts for highly efficient and durable hydrogen evolution reactions. Issue 23 (17th May 2019) - Lin, Bo; Lin, Zhiping; Chen, Shougang; Yu, Meiyan; Li, Wen; Gao, Qiang; Dong, Mengyao; Shao, Qian; Wu, Shide; Ding, Tao; Guo, Zhanhu
Abstract : Surface intercalated spherical MoS2 x Se2(1− x ) nanocatalysts with large numbers of defects and edge areas phase transition, and increased surface roughness significantly improved the HER catalytic activity. Abstract : An efficient hydrogen evolution reaction (HER) depends essentially on high-performing electrocatalysts. The aggregation of catalysts normally deteriorates their activity and stability. In this study, a two-step route was used to synthesize surface intercalated well-dispersed spherical MoS2 x Se2(1− x ) nanocatalysts. The resulting catalysts present a highly active and stable performance towards the HER with an overpotential of −143 mV at 10 mA cm −2, and a Tafel slope of 53.8 mV dec −1 . The mechanism for the enhanced HER was analyzed and was attributed to three factors: (i) large numbers of defects and edge active sites arising from the coexistence of S and Se elements; (ii) enhanced electric conductivity arising from the phase transition from the semiconducting 2H-phase to metallic 1T-phase during the intercalation process; and (iii) enlarged contact areas between active sites and electrolyte caused by the increased surface roughness due to the surface intercalation. This work not only deepens our understanding of the improved HER performance of surface intercalated catalysts, but also provides novel strategies for preparing durable electrocatalysts through surface engineering.